Pharmaceutical Assessment of Melia azedarach Gum as a Binder and Disintegrant in Immediate-Release Tablets - Frederick William Akuffo Owusu; Mariam El Boakye-Gyasi; Raphael Johnson; Yaa Asantewaa Osei; Emmanuel Asante; Desmond Asamoah Bruce Otu; Julia Afrakoma Ansong; Philomena Entsie; Marcel Tunkumgnen Bayor (The Scientific World Journal)
Excipients are components other than active ingredients that are added to pharmaceutical formulations. Naturally sourced excipients are gradually gaining preeminence over synthetically sourced excipients due to local availability and continuous supply. This study aimed to investigate the binding and disintegrating characteristics of gum extracted from the bark of Melia azedarach tree. The bark of Melia azedarach was harvested from Kwahu Asasraka in Ghana. The gum was extracted with ethanol (96%), and the percentage yield, phytochemical constituents, and flow characteristics were assessed. As a disintegrant, the gum was utilized to formulate granules at varying concentrations of 5% w/w and 10% w/w using starch as the standard. The gum was also utilized to prepare granules at varying concentrations of 10% w/v and 20% w/v as a binder, with tragacanth gum serving as the reference. Eight batches of tablets were produced from the granules. The formulated tablets from each batch were then subjected to quality control testing, which included uniformity of weight, friability, disintegration, hardness, drug content, and dissolution tests, respectively. Tannins, saponins, alkaloids, and glycosides were identified in the Melia azedarach gum. The gum had a percentage yield of 67.75% and also exhibited good flow properties. All tablets passed the uniformity of weight, friability, disintegration, hardness, dissolution, and drug content tests, respectively. According to the findings of the study, Melia azedarach gum can be utilized as an excipient in place of tragacanth and starch as a binder and disintegrant, respectively, in immediate-release tablets.